Justice in a Brave New World? - Sternlight, Jean R (2020)
As science fiction has become reality, we should consider the implications of our new technologies for our system of justice. In addition to DNA, we are now regularly using cameras, geo-tracking, facial recognition software, brain scans, computers, and much more to discern and record our physical and mental surroundings. Existing technology and more we cannot yet imagine will increasingly take the place of often unreliable evidence, such as that provided by eyewitnesses. Yet, we have given far too little thought as to how these advances should impact our civil and criminal dispute resolution systems. Historically, many justice systems have emphasized the importance of finding the truth. Our new forms of technology will arguably help us discover the truth, and thereby potentially enhance justice. Upon reflection, however, it is not clear that our scientific innovations will necessarily yield greater truth, much less justice. The products of our technology will inevitably be subject to human interpretation and argument, and justice has always been about far more than truth. This Article argues that we should focus on three critically important issues as we consider how to redesign our system of justice to accommodate our new technology. First, recognizing that judges and jurors will often lack the competence to interpret scientific data, we should rely more heavily on neutral scientific experts. Second, in light of the psychology of multiple interpretations, we will want to ensure that our technological evidence is interpreted by a diverse audience. Third, the greatest contribution of our powerful new technology may be that it helps us recognize that justice involves much more than finding the truth. Even assuming we could agree on what happened in the past, alternative visions of justice influence how a community will want to deal with past events, such as through punishment, compensation, reparations, apology, or in other ways. By deemphasizing the centrality of truth, we can focus more on other important aspects of justice, including examining motivations, healing community rifts, enunciating community norms, providing procedural justice, protecting human rights, and providing cost-effective access to our dispute resolution system. Focusing on this broad array of concerns will encourage us to reform our litigation system in creative ways and also to rely more heavily on non-litigation approaches to justice